Paroxysmal supine hypoxaemia with hyperthyroidism and atrial fibrillation: a case report of a diagnostic challenge. Issue 6 (24th May 2022) - Liu, Liang Yen; Reddy, Yogesh N V; Niven, Alexander S; Hu, Tiffany Y; Larson, Kathryn F; Mulpuru, Siva K; Cullen, Michael W
Abstract: Background: A patent foramen ovale (PFO) is a persistent embryonic defect in the interatrial septum. Platypnoea-orthodeoxia syndrome is characterized by positional hypoxaemia that is most commonly due to right-to-left shunting through a PFO. Dynamic right-to-left shunting through a PFO can also exacerbate positional hypoxaemia without platypnea-orthodeoxia syndrome. Case summary: A 78-year-old woman with hyperthyroidism and paroxysmal atrial fibrillation (AF) presented with positional hypoxaemia exacerbated by supine positioning. Diagnostic testing revealed intermittent right-to-left shunting through a PFO triggered by worsening atrial functional tricuspid regurgitation and elevated right atrial pressures. Diuresis, rate control, and thyroidectomy initially led to resolution of positional hypoxaemia, but recurrent AF episodes triggered right-to-left shunting with recurrent desaturation. Left atrial and cavo-tricuspid isthmus ablation led to restoration of normal sinus rhythm and resolution of positional hypoxaemia without PFO closure. Discussion: The clinical presentation of intermittent intracardiac right-to-left shunting can mimic decompensated heart failure with pulmonary oedema. Persistent hypoxaemia out of proportion to the degree of pulmonary oedema and minimally responsive to supplemental O2 should raise suspicion for right-to-left shunt aetiology. Positional arterial blood gases can facilitate the diagnostic evaluation of refractory hypoxaemia in cases of suspected shunting. Diagnostic imaging for PFO detection includes both transthoracic and transesophageal echocardiography with Valsalva manoeuver and agitated saline injection. Closure of a PFO for management of arterial deoxygenation syndromes should not be performed before treating other causes of arterial deoxygenation and optimizing factors that may exacerbate shunting across the PFO.